2001
DOI: 10.1053/jhep.2001.29305
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol for the prevention of first esophageal variceal hemorrhage: A lifetime commitment?

Abstract: Although ␤ blockers have had significant impact in the treatment of portal hypertension, the question of how long they should be continued for prevention of variceal hemorrhage remains unknown. Prospective studies on ␤ blockers to prevent variceal hemorrhage lack long-term follow-up, and indefinite administration of ␤ blockers for primary prevention of variceal bleeding has become standard practice. The aim of this study was to determine the outcomes of patients in whom ␤ blocker therapy was discontinued. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 18 publications
(21 reference statements)
2
45
0
6
Order By: Relevance
“…Nadolol is is usually started at a dose of 40 mg once a day (QD). Because a randomized trial showed that the risk of bleeding recurs when treatment with ␤-blockers is stopped, 59 prophylactic therapy should be continued indefinitely.…”
Section: Patients With Cirrhosis and Medium/ Large Varices That Hamentioning
confidence: 99%
“…Nadolol is is usually started at a dose of 40 mg once a day (QD). Because a randomized trial showed that the risk of bleeding recurs when treatment with ␤-blockers is stopped, 59 prophylactic therapy should be continued indefinitely.…”
Section: Patients With Cirrhosis and Medium/ Large Varices That Hamentioning
confidence: 99%
“…The efficacy of b-blockers in the prevention of bleeding or bleedingrelated mortality was the same, independently of the cause and severity of cirrhosis, ascites and size of varices. However, when propranolol is discontinued, the risk of variceal hemorrhage returns to what would be expected in an untreated population [24] . The hemodynamic response to treatment with b-blockers is considered appropriate when HVPG is decreased below 12 mmHg or by ≥ 20% of baseline values, 1-3 mo after initiation of treatment.…”
Section: Nsbbs Vs No Interventionmentioning
confidence: 95%
“…Dawka powinna być tak dobrana, aby uzyskać 25-procentowe obniżenie często-ści akcji serca (nie wolniej jednak niż 55/min), przy ciśnieniu skurczowym krwi nie niższym niż 90 mm Hg [162]. Leczenie propranololem powinno trwać całe życie i każdy pacjent powinien zostać pouczony, że nagłe odstawienie leku wiąże się z ryzykiem wystąpienia krwawienia [166].…”
Section: Nieselektywne Inhibitory Receptora Adrenergicznego βunclassified